Monitoring of chemical transformations by mass spectrometry. Issue 17 (7th September 2015) - Chen, Chun-Chi; Lin, Po-Chiao
<x xml:space="preserve">Abstract</x> During the last several decades, mass spectrometry (MS) has rapidly developed as a practical technique that can be used to monitor chemical reactions and investigate reaction mechanisms.